Are Columnar Cell Lesions the Earliest Non-Obligate Precursor in the Low-Grade Breast Neoplasia Pathway? - Strickland, Sarah; Turashvili, Gulisa (Current Oncology, 2022)
Columnar cell lesions (CCLs) of the breast comprise a spectrum of morphologic alterations of the terminal duct lobular unit involving variably dilated and enlarged acini lined by columnar epithelial cells. The World Health Organization currently classifies CCLs without atypia as columnar cell change (CCC) and columnar cell hyperplasia (CCH), whereas flat epithelial atypia (FEA) is a unifying term encompassing both CCC and CCH with cytologic atypia. CCLs have been increasingly recognized in stereotactic core needle biopsies (CNBs) performed for the assessment of calcifications. CCLs are believed to represent the earliest non-obligate precursor of low-grade invasive breast carcinomas as they share molecular alterations and often coexist with entities in the low-grade breast neoplasia pathway. Despite this association, however, the risk of progression of CCLs to invasive breast carcinoma appears low and may not exceed that of concurrent proliferative lesions. As the reported upgrade rates of pure CCL/FEA when identified as the most advanced high-risk lesion on CNB vary widely, the management of FEA diagnosed on CNB remains controversial. This review will include a historical overview of CCLs and will examine histologic diagnostic criteria, molecular alterations, prognosis and issues related to upgrade rates and clinical management.